2016
DOI: 10.18632/oncotarget.12946
|View full text |Cite
|
Sign up to set email alerts
|

Nickel chloride-induced apoptosis via mitochondria- and Fas-mediated caspase-dependent pathways in broiler chickens

Abstract: Ni, a metal with industrial and commercial uses, poses a serious hazard to human and animal health. In the present study, we used flow cytometry, immunohistochemistry and qRT-PCR to investigate the mechanisms of NiCl2-induced apoptosis in kidney cells. After treating 280 broiler chickens with 0, 300, 600 or 900 mg/kg NiCl2 for 42 days, we found that two caspase-dependent pathways were involved in the induced renal tubular cell apoptosis. In the mitochondria-mediated caspase-dependent apoptotic pathway, cyt-c, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…These findings are consistent with those of Zuo et al [36], in which nickel sulfate induces apoptosis in rat Leydig cells through activation of ROS-dependent mitochondria pathway. Likewise, the data of this study are compatible with our previous work that NiCl 2 induces apoptosis in the kidney of broiler chickens via mitochondria-dependent apoptotic pathway [37]. Interestingly, Z-YVAD-FMK (caspase-1 inhibitor) can decrease at least part of the apoptotic process.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of Zuo et al [36], in which nickel sulfate induces apoptosis in rat Leydig cells through activation of ROS-dependent mitochondria pathway. Likewise, the data of this study are compatible with our previous work that NiCl 2 induces apoptosis in the kidney of broiler chickens via mitochondria-dependent apoptotic pathway [37]. Interestingly, Z-YVAD-FMK (caspase-1 inhibitor) can decrease at least part of the apoptotic process.…”
Section: Discussionsupporting
confidence: 92%
“…Our studies indicate that HTRA2 is important in CCL2/CCR2-mediated breast cancer cell growth and invasion, but not apoptosis. HTRA2 is best known for its role as an apoptotic inducer through binding and cleaving inhibitors of apoptosis proteins (Guo et al, 2016; Kilbride and Prehn, 2013). A few studies have indicated that HTRA2 may have other cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…In the cell caspase-8 and -10 cleave and activate the effectors of proteases, such as caspase-3, -6 and -7 that act on PARP, which lead to apoptosis (Figure 1). Moreover, some members of Bcl-2 family of proteins inhibit apoptosis [114]. In addition to its importance as a biological phenomenon, defective apoptotic processes have been involved in a wide variety of diseases.…”
Section: Nickel-induced Apoptosismentioning
confidence: 99%